An adipose tissue galectin controls endothelial cell function via preferential recognition of 3-fucosylated glycans - Maller, Sebastian Matias (2019)
Upon overnutrition, adipocytes activate a homeostatic program to adjust anabolic pressure. An inflammatory response enables adipose tissue (AT) expansion with concomitant enlargement of its capillary network, and reduces energy storage by increasing insulin resistance. Galectin-12 (Gal-12), an endogenous lectin preferentially expressed in AT, plays a key role in adipocyte differentiation, lipolysis, and glucose homeostasis. Here, we reveal biochemical and biophysical determinants of Gal-12 structure, including its preferential recognition of 3-fucosylated structures, a unique feature among members of the galectin family. Furthermore, we identify a previously unanticipated role for this lectin in the regulation of angiogenesis within AT. Gal-12 showed preferential localization within the inner side of lipid droplets, and its expression was upregulated under hypoxic conditions. Through glycosylation-dependent binding to endothelial cells, Gal-12 promoted in vitro angiogenesis. Moreover, analysis of in vivo AT vasculature showed reduced vascular networks in Gal-12-deficient (Lgals12-/-) compared to wild-type mice, supporting a role for this lectin in AT angiogenesis. In conclusion, this study unveils biochemical, topological, and functional features of a hypoxia-regulated galectin in AT, which modulates endothelial cell function through recognition of 3-fucosylated glycans. Thus, glycosylation-dependent programs may control AT homeostasis by modulating endothelial cell biology with critical implications in metabolic disorders and inflammation.